Molecular signatures and transcriptional regulatory networks of human immature decidual NK and mature peripheral NK cells. Issue 9 (11th June 2014) - Wang, Fuyan; Zhou, Yonggang; Fu, Binqing; Wu, Yang; Zhang, Ruya; Sun, Rui; Tian, Zhigang; Wei, Haiming
<x xml:space="preserve">Abstract</x> Many differences exist between human immature and mature natural killer (NK) cells, but their respective molecular signatures and transcriptional regulators are relatively unknown. To gain new insights into the diversity and developmental regulation of human NK cells, we used data from high‐resolution microarrays with independent verification to describe a comprehensive comparative analysis between immature decidual NK (idNK) cells with a CD56brightCD16−T‐bet− phenotype and mature peripheral NK (mpNK) cells with a CD56dimCD16+T‐bet+ phenotype. This study shows that many novel growth factors, cytokines, and chemokines are expressed by NK cells, and they may regulate NK‐cell development or function in an autocrine manner. Notably, we present that idNK and mpNK cells are enriched for homeobox and zinc‐finger transcription factors (TFs), respectively. Additionally, many novel candidate transcriptional regulators are common to both idNK and mpNK cells. We further describe the transcriptional regulatory networks of NK cells and show that the endogenous growth factors, cytokines, and TFs enriched in idNK cells regulate each other and may contribute to idNK‐cell immaturity. Together, these findings provide novel molecular signatures for immature and mature NK cells, and the novel candidate regulators identified here can be used to describe and further understand NK‐cell differentiation and function.